2021
DOI: 10.1111/jdv.17734
|View full text |Cite
|
Sign up to set email alerts
|

A pooled analysis of randomized, controlled, phase 3 trials investigating the efficacy and safety of a novel, fixed dose calcipotriene and betamethasone dipropionate cream for the topical treatment of plaque psoriasis

Abstract: Background Plaque psoriasis is a common, chronic and relapsing inflammatory skin disease clinically characterized by erythema and scaling desquamation. As over 90% of psoriasis patients benefit from topical therapies, local treatments continue to play an eminent role in management strategies. One such topical treatment is the fixed dose combination of calcipotriol (CAL) and betamethasone dipropionate (BDP). Objectives Pooled analysis of two different phase 3 clinical trails to compare superiority regarding eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(72 citation statements)
references
References 21 publications
1
71
0
Order By: Relevance
“…Search results and study characteristics 18 articles reporting the results of 24 RCTs including 9748 patients with plaque psoriasis met the inclusion criteria. [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] (Figure 1). Due to insufficient data,so we excluded tazarotene data from one of the articles.…”
Section: Resultsmentioning
confidence: 99%
“…Search results and study characteristics 18 articles reporting the results of 24 RCTs including 9748 patients with plaque psoriasis met the inclusion criteria. [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] (Figure 1). Due to insufficient data,so we excluded tazarotene data from one of the articles.…”
Section: Resultsmentioning
confidence: 99%
“…The pooled phase 3 data demonstrate that a significantly greater proportion of patients achieved treatment success in the physician global assessment (PGA), defined as a minimum improvement of two grades to “clear” or “almost clear” disease. After 8 weeks of treatment, 43.2% of patients in the CAL/BDP PAD-cream group achieved PGA treatment success, compared to 31.9% in the CAL/BDP topical suspension/gel group ( p < 0.0001) and 5.2% in the vehicle cream group ( p < 0.0001) [ 31 ]. In one of the phase 3 trials, patients with body and scalp psoriasis were enrolled.…”
Section: Topical Delivery Of Active Compoundsmentioning
confidence: 99%
“…The trial protocol was approved by institutional review boards for each site, and all patients provided written informed consent prior to any trial-related procedures. Detailed efficacy data from phase 3 trials are presented elsewhere [ 31 , 63 ] …”
Section: Topical Delivery Of Active Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, calcipotriene (0.005% and betamethasone dipropionate 0.064%) ointment improved the presentation of psoriasis [ 267 ]. Pinter et al data showed the high effectiveness of calcipotriene and betamethasone PAD TM Technology cream with no adverse drug reaction in two Pahase 3, multicenter, randomized, investigator-blind studies [ 268 ]. Different clinical studies report that the combination of calcipotriene and betamethasone dipropionate in foam solution to be the most effective treatment for mild psoriasis [ 269 ].…”
Section: Vitamin D Paradigm In the Psoriasis Treatmentmentioning
confidence: 99%